Enhancement of sensor response by Au nanoparticles doping on ZnO tetrapod sensor - Bhoomanee C. (2014)
Zinc oxide tetrapods (T-ZnO) were synthesized using thermal oxidation technique from Zn powders mixed with hydrogen per oxide (H2O2). Through a detailed field emission scanning electron microscopy (FE-SEM), energy dispersive spectroscopy (EDS), and x-ray diffraction (XRD) showed that the T-ZnO exhibited single crystalline hexagonal wurtzite structure. The leg tip of the T-ZnO was about 8.17±1.17 μm in length and 47.80 nm in diameter. The ethanol sensors, based on the T-ZnO and the T-ZnO doped with Au nanoparticles (Au/T-ZnO), were fabricated and investigated for the ethanol sensing properties. The ethanol sensor response of the T-ZnO and the Au/T-ZnO sensors was tested at the operating temperature of 260-360oC with the ethanol concentration of 50, 100, 500, and 1000 ppm. The results showed that the Au/T-ZnO sensors exhibited exceptionally higher sensitivity than the pure T-ZnO sensors for entire ethanol concentration with optimum temperature of 340°C and 320°C, respectively. This enhancement can be explained in terms of the electron concentration of sensor in air, n0 and the reaction rate constant, kEth between the adsorbed oxygen species and the ethanol vapor due to the increase of effective surface for adsorption of ethanol on the surface. With an excellent catalytic ability, the Au nanoparticles doping on the T-ZnO sensors would result in higher reaction rate constant than the undoped T-ZnO sensors. © (2011) Trans Tech Publications.